2011
DOI: 10.1259/dmfr/19478385
|View full text |Cite
|
Sign up to set email alerts
|

Dental radiographic indicators, a key to age estimation

Abstract: Based on an appropriate knowledge of the available methods, forensic dentists can choose the most appropriate since the validity of age estimation crucially depends on the method used and its proper application. The multifactorial approach will lead to optimum age assessment. The legal requirements also have to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
150
1
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 26 publications
5
150
1
18
Order By: Relevance
“…Similar observations were noticed by Jashwant A Darji et al, who found a statistically significant sex difference in age [6]. But there could be variations in dental development between individuals and between different population groups in different regions [7].…”
Section: Discussionsupporting
confidence: 85%
“…Similar observations were noticed by Jashwant A Darji et al, who found a statistically significant sex difference in age [6]. But there could be variations in dental development between individuals and between different population groups in different regions [7].…”
Section: Discussionsupporting
confidence: 85%
“…This fact can be explained by their morphology, radiolucency and location, and because they are major elements, with well demarcated radiopacity, located in better radiographic viewing areas and with earlier formation compared to upper elements [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the anatomical location, the mandibular region has a greater and thicker bone area with fewer structures that could superimpose images during the radiographic procedure, thus contributing to a better view of the lower elements [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations